Higher maternal thyroid resistance indices were associated with increased neonatal thyroid-stimulating hormone— analyses based on the Huizhou mother-infant cohort - Li, Shuyi; Wu, Yi; Zhang, Su-juan; Li, Guoyi; Xiang, Yu Tao; Zhang, Wei-zhong; Pan, Wen-jing; Chen, Wei-qing; Hao, Yuan-tao; Ling, Wen-hua; Liu, Zhao-min (Frontiers in Endocrinology, 2022)
Abstract Objectives The aim of this study was to explore the relationship of maternal thyroid function and thyroid resistance parameters with neonatal thyroid stimulating hormone (TSH). Methods This was a longitudinal study. Singleton pregnant women without history of thyroid disorders were recruited in their first prenatal visit from Oct 2018 to Jun 2020. Maternal thyroid markers including TSH, free triiodothyronine (FT3), free thyroxine (FT4) and neonatal TSH were tested in the clinical laboratory of the hospital by electro-chemiluminescent immunoassay. Thyroid resistance indices including thyroid feedback quantile-based index (TFQI), TSH index (TSHI) and thyrotrophic T4 Resistance Index (TT4RI) were estimated according to maternal FT4 and TSH levels. Multivariable linear and logistic regression was applied to explore the associations of maternal thyroid indices with infantile TSH level. Results Total 3210 mothers were included for analysis. Multivariable linear regression indicated that maternal thyroid variables were significantly and positively associated with neonatal TSH level with the standardized coefficients of 0.085 for TSH, 0.102 for FT3, 0.100 for FT4, 0.076 for TSHI, 0.087 for TFQI, and 0.089 for TT4RI (all P<0.001). Compared with the lowest quartile, the highest quartile of TSHI (OR=1.590, 95%CI: 0.928-2.724; Ptrend=0.025), TFQI (OR=1.746, 95%CI:1.005-3.034; Ptrend =0.016), and TT4RI (OR=1.730, 95%CI：1.021-2.934; Ptrend=0.030) were significantly associated with increased risk of elevated neonatal TSH (>5 mIU/L) in a dose-response manner. Conclusion Our longitudinal data demonstrated that maternal thyroid resistance indices and thyroid hormones in the first half gestation were positively associated with neonatal TSH level. Our findings offered an additionally practical recommendation to improve current screening algorithms for congenital hypothyroidism.